Out-group prosocial giving during childhood: The role of in-group preference and out-group attitudes in a divided society. (July 2021) - Shamoa-Nir, Lipaz; Razpurker-Apfeld, Irene; Dautel, Jocelyn B.; Taylor, Laura K.
Amid protracted conflict, children are raised in divided contexts that shape the development of their intergroup attitudes and behaviors. Social identity development theory (SIDT) suggests that in-group preference may contribute to more negative out-group attitudes and behaviors in middle childhood. In such contexts, in-group favoritism may shape resource distribution, a key indicator of prosocial behavior. This study examined the predictors of resource distribution among 387 children (age: M = 9.59, SD = 2.34) of majority (Jewish) and minority (Arab-Muslim) groups in Israel. Rooted in SIDT, a multiple-group chain mediation found that the effect of age on out-group prosocial giving was serially mediated by the child's in-group symbol preference and negative out-group attitudes. The mediation held across both majority and minority groups, highlighting the underlying developmental process of prosocial giving across group lines in a divided society.